Specialized ecological interactions and plant species rarity: The role of pollinators and mycorrhizal fungi across multiple spatial scales - Philips, R.; Peakall, R.; Hutchinson, M.; Linde, C.; Xu, T.; Dixon, Kingsley; Hopper, S. (Elsevier, 2014)
Understanding the limitations to persistence and formation of populations is critical to the conservation of rare species. Engaging in specialized ecological interactions may constrain a species' distribution and abundance through limiting the availability of suitable habitat or reducing fecundity. In a generic-wide study of Drakaea (Orchidaceae), containing three common and six rare species, we tested if mycorrhizal specificity and pollinator availability is associated with intrinsic rarity across multiple spatial scales and if the ecology of common and rare species consistently differs. All Drakaea formed a mycorrhizal association with the same widely distributed species of Tulasnella, demonstrating that rarity does not arise from the mycorrhizal interaction. Drakaea are pollinated by sexual deception of thynnine wasps. Experiments at >300 sites across the geographic range of the genus revealed extreme pollinator specialization, with each species primarily pollinated by a single orchid-specific wasp species. In only two of the six rare species was the pollinator detected beyond the range of the orchid. At the scale of habitat patches, the pollinator of rare orchids occurred in fewer patches of otherwise suitable orchid habitat. Pollination rate was not significantly different between common and rare species. However, pollination rate was highest in small populations suggesting that pollinator-mediated rarity is likely to arise through patchy distribution of pollinators rather than infrequent pollen transfer in small populations. In five of the six rare species there was evidence that a specialized pollination system is contributing to rarity, demonstrating that conservation programs must prioritize the ecological requirements of pollinators.